Magnetohydrodynamic convective flow in a rotating channel (Archives of Mechanics - Test, 2000)
Combined free and forced convective flow of an electrically conducting viscous incompressible fluid in a rotating parallel plate channel with perfectly conducting walls is investigated. Exact solutions of the governing equations for the fully developed flow are obtained in closed form. It is found that the resultant shear stresses at the walls decrease with the increase in both the rotation parameter K2 and the magnetic parameter M2. The rate of heat transfer at both walls decreases with the increase in the Grashof number G.